Education planning analysis using augmented reality, virtual reality, and blockchain - Rudi Hartono; Ade Riyana; Iis Aisyah Citra Dewi; Umi Fatonah; Desy Ayu Ratna Pangesty (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The development of information technology has changed the educational landscape by providing new opportunities to enhance the learning experience. This article aims to analyze educational planning using advanced technologies such as Augmented Reality (AR), Virtual Reality (VR), and Blockchain. Through this approach, we explore the potential of integrating these technologies in optimizing educational planning, including curriculum management, student performance evaluation, and increased student participation in the learning process. The research method used is a literature study to review literature related to AR, VR, and Blockchain technology in an educational context. The results of the analysis present ideas on how the application of this technology can improve efficiency, effectiveness, and transparency in educational planning. The conclusion of this study highlights the importance of integrating advanced technologies in educational planning to support the achievement of better learning objectives.